2010
DOI: 10.1002/anie.201006486
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Efficient Fluorination of Small Molecules by SF42+

Abstract: Doubly charged, highly efficient: The use of a mass spectrometric technique specifically designed to monitor the reactions of dications has revealed that gaseous SF42+ is a powerful fluorinating agent. The fluorination of different classes of compounds (Ar, CO, CH4, C2H4, and H2) has been efficiently achieved in the gas phase (see picture). Of particular note is the formation of CF bonds in the reactions with organic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…However, conventional EI operates with electrons having kinetic energies well above the double ionization thresholds and, hence, the dications made often contain significant amounts of internal energy deposited in the ionization process, including the population of electronically excited states. [40][41][42] If the precursor ions are already generated with some excess internal energy, electron transfer in a collision with a neutral (thermal) reagent may thus lead to a conservation of the excess energy in the capture product generated from the "hot" dication generated in the source, compared to the relatively "cold" species arising from the neutral collision partner. As sketched in Scheme 2, each of these three alternative explanations may account for the experimental observation that the monocations generated by electron capture of the dication contain more internal energy than the ejection product stemming from the neutral molecule.…”
Section: +mentioning
confidence: 99%
“…However, conventional EI operates with electrons having kinetic energies well above the double ionization thresholds and, hence, the dications made often contain significant amounts of internal energy deposited in the ionization process, including the population of electronically excited states. [40][41][42] If the precursor ions are already generated with some excess internal energy, electron transfer in a collision with a neutral (thermal) reagent may thus lead to a conservation of the excess energy in the capture product generated from the "hot" dication generated in the source, compared to the relatively "cold" species arising from the neutral collision partner. As sketched in Scheme 2, each of these three alternative explanations may account for the experimental observation that the monocations generated by electron capture of the dication contain more internal energy than the ejection product stemming from the neutral molecule.…”
Section: +mentioning
confidence: 99%
“…[9] In parallel with these studies of dicationic electron transfer, laboratory studies have also revealed that molecular dications can take part in bond-forming reactivity at low collision energies in the centre-of-mass frame. [11,14,20,22,[28][29][30][31][32][33][34][35][36][37][38][39] Indeed, it has been shown that gas-phase dication chemistry can provide new pathways for the formation of specific bonds and unusual compounds. [35,40] Focusing on atomic dications, the reactive species in the current study, there has been considerable attention paid to the bond-forming chemistry of metal atom dications; such investigations were stimulated, in part, by an attempt to rationalise the activity of heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…But again, only our creativity is required to cross the bridge: For the SF 4 2+ ion, it was suggested that solvated SF 4 2+ could be formed by selective in situ photoionization of SF 4 or SF 6 or via zwitterions of the form R 2À À SF 4 2+ . The authors [19] also noted that the analogous gaseous SF 3 + ion had been reported to promote monofluorination of heterocyclic compounds (Scheme 3).…”
mentioning
confidence: 97%
“…[18] But despite the appeal of the real world MS investigations of reactions in solution, gas-phase studies have heroically survived, and are still revealing new surprising and promising reactions. The work of Price and co-workers [19] is a prime example. A doubly charged ion, SF 4 2+ , was formed and shown to perform a series of very efficient reactions (Scheme 2) that lead to the fluorination of model neutral molecules, including the activation of CH 4 to form C À F bonds.…”
mentioning
confidence: 99%